Pendampingan Manajemen Tata Kelola Keuangan Keluarga Islami di Kelurahan Kedungdoro Kecamatan Tegalsari Kota Surabaya - Sari, Tyasha Ayu Melynda; Oktaviani, Marista; Setiawan, Adhar Putra (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The aim of this community service activity is to provide financial management knowledge to the people of Kedungdoro Tegasari sub-district, Surabaya. The method used in implementing community service is through socialization and counseling activities carried out at the Surabyan I Village RT 01 RW 02 Kedungdoro Subdistrict, Tegalsari District, Surabaya City. The activity aims for housewives to understand the importance of the mother's role in the family, especially managing family finances. Family financial management is an activity of planning, managing, storing and controlling funds and assets owned by a family. Family financial management must be planned carefully so that problems do not arise in the future. The socialization and counseling activities are expected to provide knowledge to housewives in Surabyan I Village RT 01 RW 02, Kedungdoro Village, Tegalsari District, Surabaya City regarding financial management activities properly and correctly for family continuity.